Young Australians with moderate to severe mental health problems: client data and outcomes at Children and Young People's Mental Health. Issue 4 (12th May 2015) - Howe, Deborah; Batchelor, Samantha; Coates, Dominiek D.
Abstract: Aim: Almost a quarter of young Australians experience a mental health issue that may become chronic if left untreated. Children and Young People's Mental Health (CYPMH) is a specialist tertiary service for young people with moderate to severe mental health problems on the Central Coast in Australia. This paper presents an overview of client data and service use collected over a 1 year period specific to the Youth Mental Health (YMH) component of the service. Method: Client data, including demographic characteristics, service usage, presenting issues and standardized outcome measures, were analysed using SPSS. Clinicians routinely collect MH‐OAT (Mental Health Outcomes and Assessment Tools) measures at different points in a client's episode of care, and each of these measures was analysed separately. Wilcoxon Z and a series of McNemar's tests were used to report on the difference between admission and discharge scores. Results: During a designated 1 year period, 830 referrals to YMH were received. The most prevalent presenting issue was suicidal ideation followed by deliberate self‐harm and depression. A comparison of admission and discharge outcome scores shows significant improvement by discharge on a range of measures. Specifically, analysis identified significant differences between admission and discharge HoNOSCA (Health of the Nation Outcomes Scales for Children and Adolescents) and CGAS (Children's Global Assessment Scale) scores for young people aged 12–17 and HONOS (Health of the Nation Outcomes Scale) scores for young people aged 18–24. Conclusion: The clinical outcomes for young people are positive with improvements seen on a range of measures.